A Wnt-Responsive PDL Population Effectuates Extraction Socket Healing. (July 2018) - Yuan, X.; Pei, X.; Zhao, Y.; Tulu, U.S.; Liu, B.; Helms, J.A.
Stem cells residing in the periodontal ligament (PDL) support the homeostasis of the periodontium, but their in vivo identity, source(s), and function(s) remain poorly understood. Here, using a lineage-tracing mouse strain, we identified a quiescent Wnt-responsive population in the PDL that became activated in response to tooth extraction. The Wnt-responsive population expanded by proliferation, then migrated from the PDL remnants that remained attached to bundle bone, into the socket. Once there, the Wnt-responsive progeny upregulated osteogenic protein expression, differentiated into osteoblasts, and generated the new bone that healed the socket. Using a liposomal WNT3A protein therapeutic, we showed that a single application at the time of extraction was sufficient to accelerate extraction socket healing 2-fold. Collectively, these data identify a new stem cell population in the intact periodontium that is directly responsible for alveolar bone healing after tooth removal.